Bat echolocation call identification for biodiversity monitoring: a probabilistic approach. Issue 1 (20th February 2017) - Stathopoulos, Vassilios; Zamora‐Gutierrez, Veronica; Jones, Kate E.; Girolami, Mark
Summary: Bat echolocation call identification methods are important in developing efficient cost‐effective methods for large‐scale bioacoustic surveys for global biodiversity monitoring and conservation planning. Such methods need to provide interpretable probabilistic predictions of species since they will be applied across many different taxa in a diverse set of applications and environments. We develop such a method using a multinomial probit likelihood with independent Gaussian process priors and study its feasibility on a data set from an on‐going study of 21 species, five families and 1800 bat echolocation calls collected from Mexico, a hotspot of bat biodiversity. We propose an efficient approximate inference scheme based on the expectation propagation algorithm and observe that the overall methodology significantly improves on currently adopted approaches to bat call classification by providing an approach which can be easily generalized across different species and call types and is fully probabilistic. Implementation of this method has the potential to provide robust species identification tools for biodiversity acoustic bat monitoring programmes across a range of taxa and spatial scales.